2007
DOI: 10.3171/jns.2007.106.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of venous thromboembolism in 9489 patients with malignant glioma

Abstract: In patients harboring a glioma there was a very high incidence of symptomatic VTEs, particularly within 2 months of neurosurgery. The development of a VTE was associated with a 30% increase in the risk of death within 2 years. Further studies are needed to determine if risk stratification and the use of medical prophylaxis after neurosurgery improves outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(164 citation statements)
references
References 40 publications
6
153
0
5
Order By: Relevance
“…This may be especially true for brain tumor patients in whom the high VTE risk exceeds the postoperative period and stays high throughout the course of disease. [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially true for brain tumor patients in whom the high VTE risk exceeds the postoperative period and stays high throughout the course of disease. [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of deep vein thrombosis and pulmonary embolism in patients with HGG confounds separation as an independent toxicity of antiangiogenic therapies, although antiangiogenic therapy may aggravate this thrombogenic predisposition. [51][52][53][54] A retrospective review of bevacizumab plus therapy in patients with recurrent HGG suggests that concurrent use of anticoagulation appears safe without an apparent increased risk of hemorrhage. 33 In conclusion, bevacizumab as a single agent used at this dose and schedule in patients with previously treated alkylator chemotherapy-refractory recurrent 1p19q codeleted AO appears of benefit (as determined by response rate and PFS-6) for recurrent alkylator-refractory AO/ AOA.…”
Section: Original Articlementioning
confidence: 99%
“…VTE filters are placed most frequently in the inferior vena cava (IVC) to prevent a circulating clot from becoming a PE. IVC filters have been shown to be extremely effective in preventing the development of PE and in decreasing the morbidity and mortality of patients known to be harboring VTE of any kind [10,11,32,34].…”
Section: Treatment For Vtementioning
confidence: 99%
“…Patients harboring brain tumors are more likely to develop VTE than patients who have cancers in other sites (Table 1) . Studies have shown that other risk factors for VTE include age, sex, ethnicity, blood type, length of hospital stay, operative duration, and coagulation status [3,6,[8][9][10]14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Standard prophylactic measures for VTE include chemical anticoagulation, mechanical prophylaxis, and increased ambulation during the post-operative period [36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%